THE ROLE OF INTERDISCIPLINARY INTEGRATION IN DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE FOREIGN LANGUAGE TEACHERS - Rashidova Zarina Boymuroq qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article explores the significance and potential of interdisciplinary integration in developing the professional competence of future foreign language teachers. Integrating foreign language instruction with other academic disciplines not only improves language acquisition but also enhances teachers’ methodological, cultural, analytical, and technological abilities. The study highlights the importance of approaches such as CLIL (Content and Language Integrated Learning), project-based learning, and digital technologies in creating meaningful and engaging educational experiences. Furthermore, interdisciplinary learning encourages students to develop critical thinking, independent analysis, creativity, and effective communication skills. The article also discusses the benefits and challenges of implementing interdisciplinary teaching in modern education and emphasizes its role in preparing globally competent and innovative language teachers.